The dynamics and livelihood strategies of Dayak Basap people in resettlement site Bengalon - Lavraia, Haekal; Wiyanti, Dede Tresna; Hermawati, Rina (Universitas Muhammadiyah Malang, 2026)
The livelihood system is a widely discussed issue, one of which is the relationship between livelihoods with mining and resettlement. The Mining industry is known to alter the surrounding landscape, this alteration, whether by direct mining operation or indirect through related programs could lead to changes in people’s livelihoods system, these activities can be seen as a form of power interaction. The dynamics that emerge as a form of power interactions are important because they are related to livelihood conditions in society. Therefore this topic is important to study in order to produce better and holistic policies on sustainable natural resource management. The purpose of this research is to examine livelihoods of Dayak Basap people and the dynamics that occur within them. The concepts of livelihoods and power will be used to obtain a comprehensive picture of this issue. Qualitative methods with an ethnographic approach were used to conduct the research. Data collection was carried out through in-depth interviews and participatory observation. This research was conducted in RT 02, Keraitan Village, Bengalon Sub-district, which is the resettlement location of the Dayak Basap people. The results show that residents’ main livelihood sources are ecological, the dynamics within livelihood system could be seen in resource changes, as well as how residents utilize their resources through access and strategies. In this study, power negotiations could be seen in the resettlement program that initiated by mining companies and followed by the local communities. Sistem penghidupan merupakan isu yang kerap dibicarakan, salah satunya soal kaitan penghidupan dengan pertambangan dan permukiman kembali. Pertambangan diketahui dapat mengubah lanskap sekitarnya, perubahan lanskap melalui operasi pertambangan secara langsung maupun tidak langsung dengan program-programnya berpotensi mengubah sistem penghidupan masyarakat, aktivitas tersebut dapat dilihat sebagai bentuk di mana kuasa berinteraksi. Dinamika yang muncul sebagai wujud interaksi kuasa menjadi penting karena berhubungan dengan kondisi penghidupan pada masyarakat. Oleh karena itu, topik ini penting dikaji guna menghasilkan kebijakan yang lebih baik dan holistik perihal pengelolaan sumber daya alam yang berkelanjutan. Tujuan penelitian ini adalah untuk mengkaji penghidupan warga Dayak Basap dan dinamika di dalamnya. Konsep penghidupan dan kuasa digunakan untuk menangkap gambaran yang komprehensif terkait isu ini. Metode kualitatif dengan pendekatan etnografis digunakan untuk melaksanakan penelitian. Pengumpulan data dilakukan melalui wawancara mendalam serta observasi partisipatif. Penelitian dilakukan di RT 02, Desa Keraitan, Kecamatan Bengalon yang merupakan lokasi permukiman kembali warga Dayak Basap. Hasil penelitian menunjukkan bahwa sumber penghidupan yang bersifat ekologis merupakan sumber utama warga, dinamika pun dapat terlihat dalam perubahan sumber, juga bagaimana warga memanfaatkan sumber lewat akses dan strategi yang dilakukannya. Dalam kajian ini negosiasi kuasa dapat terlihat dalam program resettlement yang diinisiasi perusahaan tambang dan diikuti oleh masyarakat setempat.